Breast metastasis from primary hand rhabdomyosarcoma - Nevien Ragae Fares; Tassnim Osama Mohammed (The Egyptian Journal of Radiology and Nuclear Medicine, 2024)
Abstract Background Rhabdomyosarcoma can occur almost anywhere in the body; however, the most common primary sites include the head and neck (50%), genitourinary tract (~ 25%), and extremities (~ 15%). Approximately 20% of rhabdomyosarcoma patients present with metastases at diagnosis, most commonly to the lungs, bone marrow, and lymph nodes. Rhabdomyosarcoma metastasizing to distant sites such as the breast highlights its aggressive behavior. Case presentation A 20-year-old girl presented with left-hand swelling and pain which was unfortunately excised without imaging evaluation. Postoperative histopathology revealed a malignant spindle cell tumor. After two months, the patient complained of rapidly growing bilateral breast masses. As regards the patient’s age diagnostic ultrasound was done that revealed bilateral breast masses with bilateral axillary lymphadenopathy (Fig. 1), and then, magnetic resonance imaging was done that revealed bilateral breast masses of malignant criteria and pathological left axillary lymph nodes (Fig. 2). An ultrasound-guided biopsy was taken from both breast masses which revealed a metastatic malignant spindle cell tumor. After immunophenotyping, the diagnosis of rhabdomyosarcoma is established. Unfortunately, a metastatic work-up was done that revealed a visceral and nodal metastasis as well as a myocardial deposit (Fig. 3). Conclusions Metastasis of rhabdomyosarcoma to the breast is rare and occurs in young women as in our case with mainly primary site in limbs. It is important to be clinically aware of the risk of breast metastasis in female patients with primary extra-mammary rhabdomyosarcoma.